Structural and functional changes in cardiovascular system at arterial hypertension in persons exposed to ionising radiation. (18th April 2006) - Takhauov, R.M.; Karpov, A.B.; Semenova, Yu.V.; Leonov, V.P.; Babakina, N.V.; Popov, S.V.
The purposes of this research were: (1) to carry out the comparative evaluation of indices of the morphofunctional condition of the cardiovascular system (CVS) in patients with arterial hypertension (AH) exposed to ionizing radiation, taking into account the occurrence of peripheral arterial atherosclerosis and the spread of traditional risk factors of cardiovascular diseases (CVD); (2) to determine interaction between the structural and functional indices of the CVS and IR influence. Unbiased sampling of patients with mild and moderate AH (n = 100) in the cohort exposed to sources of IR in the workplace was undertaken, with investigation of heart rate variability, and scintiangiography of large arteries of elastic type to evaluate their elastic-tonic properties and the functional condition of the endothelium. Comparison of the spread rate of risk factors of cardiovascular pathology formation revealed a more frequent occurrence of tobacco smoking, shiftwork, and a high level of psychoemotional overstrain in persons in contact with IR sources in the workplace. The results revealed a tendency to increased arterial blood pressure, longer duration of AH, and more significant structural and functional changes in the CVS in an unbiased sample of persons suffering from AH exposed to IR.